Minimally invasive technique for tendo-achillis lengthening (Dr Kothari's modification of White's technique) - Kothari SY; Gupta A (Indian Journal of Physical Medicine & Rehabilitation, 2011)
Tendo-achillis is a strong plantar flexor of the foot, therefore important for walking and running purposes. Correction of equinus contracture by tendo-achillis lengthening is essential for the proper biomechanics of the entire lower limb, both in standing and walking. Various techniques are available for TA lengthening. Z-plasty may be done in sagittal plane or coronal plane according to biomechanical or functional needs. In White's technique the tendon slides on itself and gets adjusted according to the level of spasticity. We modified the procedure by giving two smaller incisions so as to minimize skin complications.